Deteksi Dini Conventional Smear dan Liquid Based Cytology dalam Upaya Pencegahan Kanker Serviks: Literature Review - Ayu Indah Lestari; Budi Hidayat (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2019)
Background: Cervical cancer is the most common cancer among women. Cervical cancer mortality is also an indicator of health success, because 86% of all deaths due to cervical cancer are in developing, low and middle income countries. Cervical cancer is caused by the Human Papilloma Virus (HPV), one of the most common sexually transmitted infections in the world.Objective: This literature review aims to describe early detection of pap smear (Conventional Smear and Liquid Based Cytology) as prevention of cervical cancer.Method: This review used the literature review method to search all related and relevant articles in PubMed, ProQuest, Science Direct and Portal Garuda with publications between 2008-2018.Results and Discussion: Liquid Based Cytology sensitivity (88%) is much higher than that reported in Conventional Smear (20-30%), Liquid Based Cytology examination has the potential to increase sensitivity in the diagnosis of endometrial carcinoma.Conclusion: Although conventional smear sensitivity is lower than Liquid Based Cytology, the price of conventional smear is more affordable for the community, and the target of Liquid Based Cytology is adapted for the upper middle class. To improved conventional smear effectiveness can be accompanied by IVA examination so that it is not repeated, more practical, and higher validity.